2015
DOI: 10.1080/00223980.2015.1039474
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Negative Affective Conditions in Adults: Is There Any Room for Hope in Predicting Anxiety and Depressive Symptoms?

Abstract: This study examined the role of hope in understanding the link between loneliness and negative affective conditions (viz., anxiety and depressive symptoms) in a sample of 318 adults. As expected, loneliness was found to be a significant predictor of both anxiety and depressive symptoms. Noteworthy, hope was found to significantly augment the prediction of depressive symptoms, even after accounting for loneliness. Furthermore, we found evidence for a significant Loneliness × Hope interaction effect in predictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 33 publications
8
34
0
2
Order By: Relevance
“…For example, in a previous study, the relationship between emotional neglect, sexual maltreatment, and behavioral maltreatment with 3 dimensions of depression and anxiety symptoms (general distress, anhedonic depression, and anxious arousal) was examined. The results indicated that emotional neglect was accompanied by 3 dimensions, behavioral maltreatment with two dimensions (general distress and anxious arousal), and physical maltreatment only with anxious arousal (Infurna et al, 2016). Another study suggested that different kinds of traumatic experiences had different impacts on emotion regulation.…”
Section: Plain Language Summarymentioning
confidence: 97%
“…For example, in a previous study, the relationship between emotional neglect, sexual maltreatment, and behavioral maltreatment with 3 dimensions of depression and anxiety symptoms (general distress, anhedonic depression, and anxious arousal) was examined. The results indicated that emotional neglect was accompanied by 3 dimensions, behavioral maltreatment with two dimensions (general distress and anxious arousal), and physical maltreatment only with anxious arousal (Infurna et al, 2016). Another study suggested that different kinds of traumatic experiences had different impacts on emotion regulation.…”
Section: Plain Language Summarymentioning
confidence: 97%
“…It was first developed by Goldberg to identify mental disorders in different settings, including health facilities (Noorbala, Mohammad, & Bagheri Yazdi, 2002). It measures general health and well-being (Hjelle et al, 2019). Goldberg and Hiller provided a revised version of the questionnaire.…”
Section: General Health Questionnaire (Ghq)mentioning
confidence: 99%
“…Findings from a number of studies have pointed to a reliable association between loneliness and anxiety (e.g., Chang, 2013Chang, , 2017Zawadzki, Graham, & Gerin, 2013). For example, in a study of young adults, Muyan et al (2016) found that loneliness was associated with greater anxious symptoms. Similarly, loneliness has been linked to depression (e.g., Cacioppo, Hughes, Waite, Hawkley, & Thisted, 2006;Chang, 2013Chang, , 2017.…”
Section: Loneliness and Unhappy Conditions In Adultsmentioning
confidence: 99%